PAULUS DAN PERNIKAHAN: TINJAUAN TEOLOGIS TERHADAP PANDANGAN RASUL PAULUS MENGENAI PERNIKAHAN KRISTEN - Esty Kurniawaty; Prionaray Bram M; Juprianto Palayukan (Sekolah Tinggi Agama Kristen Imanuel Bitung, 2026)
Marriage has been designed by God with the purpose of human goodness. In Christian family, marriage so important. Marriage has been mandated by God to humans from the beginning “Be fruitful, and multiply, and replenish the earth...” (Genesis 1:28). Marriage is given, so husband and wife can strengthen each other, by living together faithfully in lack and love, in joy and sorrow. Husband and wife can know each other in love and through bodily interaction can strengthen the fellowship of their hearts and lives. Because marriage is one of God's mandates, humans should maintain the sanctity of marriage. Thus, married life will be in harmony with the basic Fear of God. However, there have been many Christian marriages that have ended in divorce. Views of the blessings associated with biblical marriage are shrinking. In fact, marriage is a sacred covenant. Therefore, the problem in this paper is how Paul's theology regarding marriage is viewed from the book of 1 Corinthians 7. The writing method used is qualitative, through library research with the aim that husband and wife understand the meaning, purpose, and a basis that becomes firmness, the example of Christ's love, which is also the result of this discussion.